Fabrication, efficiency loss analysis, and simulation-based optimization of semi-transparent perovskite solar cell modules for photovoltaic windows - Huang, Yuqi; Shen, Chao; Cai, Chunguang; Zhu, Wenzhi; Liang, Yongqi; Kalogirou, Soteris A.; Wang, Julian (My University, 2025)
The urgent demand for carbon neutrality in buildings has propelled semi-transparent photovoltaic windows to become a pivotal component of Building Integrated Photovoltaics technology. Despite the unique advantages of perovskite materials, such as tunable bandgap, high absorption coefficient, and solution processability, their practical application is hindered by significant efficiency degradation during large-area fabrication. This study proposes a multi-scale collaborative manufacturing strategy, integrating air-knife blade coating, magnetron sputtering, and pulsed laser etching, to successfully fabricate a 25 cm2 semi-transparent perovskite solar cell module (ST-PSCM). The module achieves a 27.2 % average visible light transmittance (AVT), a 2.44 % power conversion efficiency (PCE), and a color rendering index of 82, meeting the functional requirements for building applications. Through a circuit quantification model that incorporates radiative recombination, non-radiative recombination, and resistive losses, the study identifies bulk recombination (65.17 %) and series resistance losses (29.53 %) as the primary mechanisms of efficiency loss. Furthermore, leveraging the Solar Design optoelectronic coupling simulation platform, the temperature and light intensity response characteristics of the ST-PSCM were systematically analyzed. Through a layer-by-layer optimization of thicknesses of each functional layer, the module achieved a PCE of 2.80 % at 38.3 % AVT. This study provides a scalable manufacturing approach for the large-scale application of semi-transparent perovskite photovoltaic windows, offering significant practical value for advancing the development of near-zero energy building technologies.
Keywords: Efficiency loss mechanisms; Semi-transparent perovskite solar cell modules; Solar design; Temperature and light intensity performance; Thickness optimization